(untitled) (Práxis Educativa, 2020)
In this article we offer an analysis of the production on education policy from a comparative perspective of authors based on Argentine institutions for the period 2001-2015. A base of articles obtained from a sample of academic journals - including national and foreign journals specialized in education - was studied to establish its distribution regarding the topics addressed, geographical focus of the articles, and institutional membership of the authors. Secondly, an analysis was made of the theoretical and methodological approaches of a subset of articles, those that take as their object of study the policies of the period 1990-2015 for basic education in Latin America. Keywords: Education policy. Comparative perspective. Theoretical and methodologic approaches. Argentina.